Natural Bizbenzoquinoline Derivatives Protect Zebrafish Lateral Line Sensory Hair Cells from Aminoglycoside Toxicity - Kruger, Matthew; Boney, Robert; Ordoobadi, Alexander J.; Sommers, Thomas F.; Trapani, Josef G.; Coffin, Allison B. (Frontiers in Cellular Neuroscience, 2016)
Moderate to severe hearing loss affects 360 million people worldwide and most often results from damage to sensory hair cells. Hair cell damage can result from aging, genetic mutations, excess noise exposure, and certain medications including aminoglycoside antibiotics. Aminoglycosides are effective at treating infections associated with cystic fibrosis and other life-threatening conditions such as sepsis, but cause hearing loss in 20-30% of patients. It is therefore imperative to develop new therapies to combat hearing loss and allow safe use of these potent antibiotics. We approach this drug discovery question using the larval zebrafish lateral line because zebrafish hair cells are structurally and functionally similar to mammalian inner ear hair cells and respond similarly to toxins. We screened a library of 502 natural compounds in order to identify novel hair cell protectants. Our screen identified four bisbenzylisoquinoline derivatives: berbamine, E6 berbamine, hernandezine, and isotetrandrine, each of which robustly protected hair cells from aminoglycoside-induced damage. Using fluorescence microscopy and electrophysiology, we demonstrated that the natural compounds confer protection by reducing antibiotic uptake into hair cells and showed that hair cells remain functional during and after incubation in E6 berbamine. We also determined that these natural compounds do not reduce antibiotic efficacy. Together, these natural compounds represent a novel source of possible otoprotective drugs that may offer therapeutic options for patients receiving aminoglycoside treatment.